SOME ASPECTS OF FAMILY FUNCTIONING AND QUALITY OF LIFE IN PATIENTS WITH NEUROTIC DISORDERS - Herasymenko, L. (World of Medicine and Biology, 2014)
Determined that the indicators of quality of life is an important criterion for evaluating the therapy and allows to estimate not only the dynamics of psychopathology in conjunction with the social functioning of the individual and expands the range of diagnostic, therapeutic criteria for psychiatric psychotherapy practice. The results of the study determined that the quality of life as patients with neurotic disorder and their partners have an impact on family functioning and should be considered during diagnostic and therapeutic psychotherapeutic interventions.
Keywords: neurotic disorder; family functioning; quality of life